2013
DOI: 10.1093/humupd/dmt032
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct low-molecular-weight heparin to improve live birth rate after recurrent implantation failure: a systematic review and meta-analysis

Abstract: BACKGROUND Poor fertility outcomes in women with recurrent implantation failure (≥ RIF) present significant challenges in assisted reproduction, and various adjuncts, including heparin, are used for potential improvement in pregnancy rates. We performed this systematic review and meta-analysis to evaluate the effect of low-molecular-weight heparin (LMWH) on live birth rates (LBRs) and implantation rates (IRs) in women with RIF and undergoing IVF. METHODS Studies comparing LMWH versus control/placebo in women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 50 publications
1
81
1
1
Order By: Relevance
“…The effect of heparin treatment in assisting some pregnancies could lie in its ability to block the heparin binding site of HPV, 47 and HPV status may provide clarity to the heparin therapy debate. 48 Similarly, salicylic acid is widely prescribed and appears effective in pre-eclamptic pregnancies. 49 Salicyclic acid is also used as an inexpensive treatment for cutaneous warts, possibly affecting HPV E6 and E7 protein action on cyclooxygenase-2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of heparin treatment in assisting some pregnancies could lie in its ability to block the heparin binding site of HPV, 47 and HPV status may provide clarity to the heparin therapy debate. 48 Similarly, salicylic acid is widely prescribed and appears effective in pre-eclamptic pregnancies. 49 Salicyclic acid is also used as an inexpensive treatment for cutaneous warts, possibly affecting HPV E6 and E7 protein action on cyclooxygenase-2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,8,[10][11][12] It has also been seen that the treatment with LMWH has been preferred to unfractionated heparin. 3,4,8,11,[13][14][15][16][17][18][19][20] The recommendations for anticoagulation therapy for acquired thrombophilia are very well defined and have found to have a significant positive impact on pregnancy outcome. 2,4,8,12,15,22,23 Heparin is a glycosaminoglycan that binds to antithrombin thereby inactivating thrombin, Factor IXa and Factor Xa resulting in expression of anticoagulant response.…”
Section: Resultsmentioning
confidence: 99%
“…The ease of administration and better bioavailability of low molecular weight heparin has resulted in conduct of various trials favouring its use over unfractionated heparin in treatment of pregnant women with thrombophilia. 3,4,8,[13][14][15][16][17][18][19][20] Low dose ecosprin acts by blocking the conversion of arachdonic acid to thromboxane A2. Hence, there is reduction in synthesis of Thromboxane A2.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, a systematic review and a meta-analysis including two RCTs and one quasi-randomized trial showed a significant improvement in the LBR (risk ratio (RR) ¼ 1.79, 95% confidence interval (CI) ¼ 1.10-2.90, P ¼ 0.02) and a reduction in the miscarriage rate (RR ¼ 0.22, 95% CI ¼ 0.06-0.78, P ¼ 0.02) with LMWH compared with controls. However, the beneficial effect of LMWH was not significant when only studies with unexplained RIF were pooled [28]. Finally, a recent Cochrane review [33] including three RCTs, of which two consisted of women with 3 RIF and one consisted of women with unexplained infertility undergoing their first IVF cycles, reported similar findings: when a fixed effect analysis was used as a statistical model, peri-implantation heparin was associated with an improvement in live birth rate compared with placebo or no heparin (odds ratio (OR) 1.77, 95% confidence interval (CI) 1.07 to 2.90) and also an improvement in the clinical pregnancy rate (OR 1.61, 95% CI 1.03 to 2.53) but authors noted low quality of evidence.…”
Section: Heparinmentioning
confidence: 92%
“…In the last decade it has been proposed also as an adjunct in assisted reproduction since it has been speculated that heparin may improve the intrauterine environment in sub-fertile women. The proposed mechanism is that heparin may improve decidualization with an associated activation of growth factors such as IGF-1, heparinbinding epidermal growth factor and cytokine expression in the endometrium promoting embryo implantation through trophoblast invasion and proliferation, promoting successful pregnancy [28,29]. Heparin is administered trans-dermally in the form of unfractionated or low-molecular-weight heparin (LMWH) which is derived from heparin by depolymerization, showing similar activity but with increased bioavailability and half-life.…”
mentioning
confidence: 99%